2014
DOI: 10.1016/j.bbi.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion as a predictor of interleukin-6 response to acute psychosocial stress

Abstract: We examined the hypothesis that self-compassion is associated with lower levels of stress-induced inflammation. On two consecutive days, plasma concentrations of interleukin-6 (IL-6) were assessed at baseline and at 30 and 120 minutes following exposure to a standardized laboratory stressor in a sample of 41 healthy young adults. Participants who were higher in self-compassion exhibited significantly lower day 1 IL-6 responses, even when controlling for self-esteem, depressive symptoms, demographic factors, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 36 publications
6
88
0
1
Order By: Relevance
“…Initial placement of the catheter was followed by a resting period of 30 min to ensure recovery from potential stress response to catheter placement or traveling to the laboratory. Because previous research has found that IL-6 peaks 120 minutes post-stressor (von Kanel, Kudielka et al 2006, Breines, Thoma et al 2014, Rohleder 2014), blood was drawn at baseline, 30, and 120 min following the TSST on both study days.…”
Section: Methodsmentioning
confidence: 99%
“…Initial placement of the catheter was followed by a resting period of 30 min to ensure recovery from potential stress response to catheter placement or traveling to the laboratory. Because previous research has found that IL-6 peaks 120 minutes post-stressor (von Kanel, Kudielka et al 2006, Breines, Thoma et al 2014, Rohleder 2014), blood was drawn at baseline, 30, and 120 min following the TSST on both study days.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Breines et al (2014, 2015) reported evidence of this effect. Adults with higher self-compassion exhibited lower interleukin-6 production, an inflammatory marker, and lower salivary alpha amylase production, a marker of sympathetic nervous system activation, in response to the Trier Social Stress Test (TSST), an acute laboratory social stressor which participants generally interpret as threatening to social status (Breines et al, 2014, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Social support is one mechanism that helps to protect adolescents from these social threats and is linked to healthy adjustment (Hauser & Bowlds, 1990). Self-compassion may be viewed as social support turned inwards (Breines et al, 2014), providing a way in which adolescents can directly support themselves emotionally . Therefore, one would expect that those with higher self-compassion would evidence a diminished physiological stress response in the presence of a social stressor than those with lower self-compassion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, individuals with considerably high self-compassion showed substantially low autonomic response and anxiety when they were exposed to acute psychosocial threat (Neff et al, 2007a; Breines et al, 2014). Vettese et al (2011) determined that self-compassion was reported to mediate the relationship between the experience of maltreatment in childhood and later emotion dysregulation.…”
Section: Introductionmentioning
confidence: 99%